Knee Flexors Maximum Effective Angle Variation after Anterior Cruciate Ligament Reconstruction with Hamstring Graft (International Journal of Physiotherapy, 2021)
Background: During the anterior cruciate ligament reconstruction, the graft is taken from the distal hamstring tendon, which causes morphological and neurological changes in these muscles, particularly on the maximum effective angle of the knee flexors. The present study investigates changes in knee flexor following anterior cruciate ligament reconstruction with a hamstring graft.Methods: Two populations participated in this study, a healthy group and a group that underwent anterior cruciate ligament reconstruction with a hamstring graft. First, the test group underwent two postoperative assessments on an isokinetic device at 3 and 6 months. Next, we compared the test group at 3 and 6 months with the control group to highlight the differences between the knee flexors maximum effective angle. And finally, we have compared the knee flexors maximum effective angle with the moment of maximum force to determine whether these two values are related.Results: The maximum effective angle is decreased regardless of the duration of rehabilitation (ρ= 0.0019, ρ = 0.037). It does not change significantly during rehabilitation (ρ = 0.29). It does not depend on the strength gained during rehabilitation but on a neuromotor change due to the morphological changes caused by surgery.Conclusion: The study results show that anterior cruciate ligament reconstruction with hamstring graft causes a decrease in knee flexor maximum effective angle.